Character strengths and psychological vulnerability: The mediating role of resilience - EKŞİ, HALİL (SPRINGER, 2021)
The present study examined the relationships between character strengths and psychological resilience and psychological vulnerability. The sample consisted of 381 high school students (164 males and 217 females) ranging in age from 14 to 18 years (Mean=15.63, SD=1.12). Character Growth Index, the Brief Resilience Scale and Psychological Vulnerability Scale were used as measures to collect the data. Structural Equation Modeling and bootstrapping methods were used to examine the mediating role of psychological resilience in relationships between character strengths and psychological vulnerability. In the structural model, certain character strengths i.e. wisdom, courage, optimism, and, calmness were found to increase psychological resilience, and psychological resilience decreased psychological vulnerability. Also, psychological resilience fully mediated the relationship between the character strengths of wisdom, courage, optimism, and calmness and psychological vulnerability. The results of the bootstrapping analysis showed that the indirect effects of the character strengths of wisdom, courage, optimism, and calmness on psychological vulnerability were significant. Based on these results, we conclude that high levels of wisdom, courage, optimism and calmness accompanied by psychological resilience may lead to decreased psychological vulnerability. The theoretical and practical implications for researchers and practitioners and limitations are discussed.
Keywords: Character strengths; Psychological vulnerability; Resilience; Adolescents; ACTION INVENTORY; SELF-ESTEEM; SCALE; ADOLESCENTS; VALIDATION; CHILDREN; BENEFITS; HEALTH; VALUES